The use of real time ultrasound scanning as a teaching method of anatomy in an undergraduate sonography and medical imaging degree in an Australian university. Issue 1 (February 2016) - Bowman, A.; Lawson, C.; McKillup, S.
Abstract: Background: Real-time ultrasound scanning is increasing in popularity as a teaching tool for human anatomy because it is non-invasive, offers real-time 3-D anatomy and is cheaper than dissections. Aim: To assess real-time ultrasound scanning as a teaching method of human anatomy, and to determine what teaching methods medical imaging and sonography students consider effective for understanding human anatomy. Method: Surveys were distributed to two consecutive cohorts of first year medical imaging and medical sonography students at CQUniversity. Participation was voluntary. Comparisons among teaching methods were made using repeated measures ANOVA. Results: Real-time ultrasound scanning was the most preferred method of delivery for anatomy classes overall especially compared to computer programs, videos, 3-D radiological images and dissection. Specifically, students indicated that ultrasound scanning was the preferred method to encourage learning from experience ( F 7, 231 = 2.942, p = 0.006), to develop team skills ( F 7, 231 = 4.550, p < 0.006), to follow complex instructions ( F 7, 231 = 4.656 p < 0.001) and to appreciate anatomical variation ( F 7, 231 = 2.067, p = 0.048). Dissection was the least favoured teaching method. Conclusion: Real-time ultrasound scanning is a useful tool for teaching anatomy, and animal dissections are a poor substitute for the use of human cadavers. Highlights: Real-time ultrasound scanning is a valid teaching tool for human anatomy. Real-time ultrasound is preferred by students compared to other teaching methods. Dissection is the least favoured method to learn anatomy. Ultrasound encourages learning from experience and develops team skills.